ThisEase a proposed peri-urban EcoHealth Center and Wellness Facility through synergy-generative architecture - Del Pilar, Mihaila Ianeska Dy
The increased incidence of outbreaks over the recent decades have reinforced nature as a vital determinant of health. The COVID-19 pandemic unveiled insufficiencies in terms of healthcare capacities and preparedness levels in the Philippines. With the emergence and recurrence of infectious diseases (EIDs and RIDs), there is a need to better understand, prevent and prepare against epidemics even in small scale communities. Guided by socio-ecological interactions, the transdisciplinary field of EcoHealth serves as a holistic approach that is viable in addressing these interlaced human-environment health issues. This study intends to explore a synergistic architectural approach in the design of an ecohealth center with a wellness facility that aim to enhance the human environment relationship while considering preventive healthcare measures in a local peri-urban community such as Nuvali, Laguna. The project will analyze the factors that contribute to the onset of infectious diseases through the EcoHealth perspective, develop an architectural framework that addresses the spatial needs and programming of an ecohealth center and wellness facility towards a holistic community-level capacity building, and integrate effectively preventive healthcare measures based on the principles of EcoHealth in order to translate into a synergistic ecohealth center and wellness facility in Nuvali, Laguna. The project will unveil an EcoHealth-focused peri-urban center that can be a synergistic architectural solution in bridging the often overlooked gaps between the domains of human, environment, and preventive health considerations in leveraging disease prevention and holistic wellness.